Buckling and yield strength estimation of architected materials under arbitrary loads. (1st November 2022) - Andersen, Morten N.; Wang, Yiqiang; Wang, Fengwen; Sigmund, Ole
Abstract: Buckling strength estimation of architected materials has mainly been restricted to load cases oriented along symmetry axes. However, realistic load scenarios usually exhibit more general stress distributions. This study employs local member analyses to estimate the buckling strength surface of stretch-dominated lattice structures. As an integral part of the method, the yield strength surface is also determined. Local members are analyzed under different boundary conditions, i.e., simply-supported, clamped as well as rotational springs accounting for lattice topologies. The local member estimations are compared with accurate but expensive numerical linear microstructural buckling analyses for different loadings. The local member approach provides a valuable tool to quickly estimate the microstructural buckling strength of stretch-dominated lattice structures, especially for applications where the stress state is non-uniform such as infill in additive manufacturing. Using the local member approach, we compute the entire buckling strength surfaces of an orthotropic bulk modulus optimal plate, an isotropic stiffness optimal plate, and an isotropic truss lattice structure subjected to rotated uni-axial loads. All the considered lattice structures possess high buckling strength anisotropy. In addition, the isotropic stiffness optimal plate structure possesses a near-isotropic yield strength surface while the truss counterpart possesses an anisotropic one. Inspired by the buckling strength surface calculations, we further propose a new isotropic plate lattice configuration with enhanced buckling strength isotropy without stiffness or yield strength deterioration.